Politics in Language and Language in Politics. Glossary of Sensitive Language for Internal and External Communication of the European Parliament - Blanche, Evelina; Bičkauskaitė, Rūta (Vertimo studijos, 2021)
The article discusses the key principles invoked and issues addressed while drafting the Lithuanian language version of the Glossary of Sensitive Language for Internal and External Communication of the European Parliament. As a first step, it offers a short overview of the three categories of terminology presented in the Glossary related to disability, LGBTQ+, and race, ethnicity and religion. Thereafter it touches upon the issues pertaining its use in the light of current societal trends, correct and clear language requirements, influence of foreign languages and human rights. The article argues that sensitive language is imperative in communication with disadvantaged groups continuously marred by prejudices, fears, and stereotypes. Based on this proposition the article emphasizes the importance of political correctness as personal stance. At the same time, it exemplifies limitations thereof that could be triggered by the language system itself.